Illegal harvest of marine resources on Andros Island and the legacy of colonial governance - Silvy, Elizabeth H. (The British journal of criminology, 2018)
We used a qualitative case study on Andros Island, The Bahamas, to explore illegal harvest of marine resources as it relates to colonialism. Data collection included interviews with local informants who participated in harvest of marine resources (n = 62), observations and field notes. Residents considered illegal harvest of marine resources ubiquitous, and viewed using marine resources when and where they choose as an appropriate continuation of traditional livelihoods. Residents also perceived both overharvest and regulations constraining harvest as issues pertaining to outside colonial influences. These findings suggest an increased focus on colonial governance may provide insight and more sustainable solutions for marine resource management where traditional harvesting activities are designated as illegal by outside regulators.